como resolver essa equação acima?
Anexos:
![](https://pt-static.z-dn.net/files/d19/e741d5fc37cc69bf1f199ab2fe8038c9.jpg)
Soluções para a tarefa
Respondido por
1
x = -3 -y
3x + y = 1
3( -3 -y) +y = 1
y= -5
3x -5 = 1
x = 2
(x,y) = (2,5)
2 - 5 = -3
3 X 2 -5 = 1
3x + y = 1
3( -3 -y) +y = 1
y= -5
3x -5 = 1
x = 2
(x,y) = (2,5)
2 - 5 = -3
3 X 2 -5 = 1
karoline234:
muitooo obrigado amor❤
Perguntas interessantes
Artes,
11 meses atrás
Ed. Técnica,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Filosofia,
1 ano atrás